Dimensão afetiva e projetos vitais de jovens estudantes de ensino superior - Cristina Satiê de Oliveira Pátaro (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This paper discusses possible relations between the strategies of conflict resolution and the construction of youth purpose, through analysis of the influence of feelings and emotions in thought. It was investigated how the emotions and feelings related to the interests and concerns of youth configure in reasoning. Data were collected by semi-structured interviews conducted with 20 youth (20-24 years old), academic students of Paraná state. From the analysis, based on theory of Organizing Models of Thinking, relations were identified between the nature of the interests and concerns of youth and the feelings and emotions. The results show that the construction of youth purpose may be related to how young people perceive conflict, so that considerations are drawn about the inseparability between affect and cognition, and implications to educational processes aimed at youth.